2021
DOI: 10.3389/fmicb.2021.630841
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Bacillus licheniformis on Heat Stroke in Rats by Sustaining Intestinal Barrier Function and Modulating Gut Microbiota

Abstract: Heat stroke (HS) models in rats are associated with severe intestinal injury, which is often considered as the key event at the onset of HS. Probiotics can regulate the gut microbiota by inhibiting the colonization of harmful bacteria and promoting the proliferation of beneficial bacteria. Here, we investigated the preventive effects of a probiotic Bacillus licheniformis strain (BL, CMCC 63516) on HS rats as well as its effects on intestinal barrier function and gut microbiota. All rats were randomly divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Recent reports have demonstrated that B. licheniformis CGMCC 1.3448 enhances epithelial barrier integrity in laying hens ( 18 ) and B. licheniformis B26 in broiler chickens ( 52 ), characterized by the increased expression of ZO -1, Occludin and Claudin-1 at the mRNA level in the gut. A study suggested that B. licheniformis preadministration alleviated intestinal injury and improved gut barrier function during and after heat stroke (HS) onset ( 53 ). This research indicated that B. licheniformis maintained the mucosal barrier and intestinal health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated that B. licheniformis CGMCC 1.3448 enhances epithelial barrier integrity in laying hens ( 18 ) and B. licheniformis B26 in broiler chickens ( 52 ), characterized by the increased expression of ZO -1, Occludin and Claudin-1 at the mRNA level in the gut. A study suggested that B. licheniformis preadministration alleviated intestinal injury and improved gut barrier function during and after heat stroke (HS) onset ( 53 ). This research indicated that B. licheniformis maintained the mucosal barrier and intestinal health.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the intestinal microbiota was rebalanced. Another study indicated the protective role of B. licheniformis CMCC 63516 on heat stroke in rats [ 59 ]. The B. licheniformis was introduced in quantity 10 8 CFU/mL twice daily for 7 days.…”
Section: Probioticsmentioning
confidence: 99%
“…bulgaricus) , and L. acidophilus improved ischemia via the mechanisms involved in anti-oxidation and anti-inflammation and ameliorated neurological deficits [ 75 , 76 ]. The intake of probiotic Bacillus licheniformis CMCC 63516 showed preventive effects on heat stroke in rats by sustaining intestinal barrier function, such as increasing tight junctions and decreasing intestinal injury and modulating gut microbiota, e.g., increasing the ratio of Lactobacillus and Lactococcus in the gut microbiota [ 77 ]. Moreover, the protective effect of Lactobacillus amylovorus DSM 16698T (ILA) on cerebral ischemia reperfusion injury in rats was observed through attenuating cerebral infarction volume and neural cell apoptosis, decreasing the levels of MDA and TLR-4, and increasing superoxide dismutase (SOD) activity [ 78 ].…”
Section: Probiotics and Their Potential Role In Cvdmentioning
confidence: 99%
“…The abovementioned research regarding the role of probiotics in CHD revealed that administration of pure probiotic strains or the co-supplementation of probiotics with other products attenuated levels of hs-CPR and other inflammatory factors [ 67 , 68 , 69 , 70 , 71 ]. In addition, the anti-inflammatory effects of probiotics on stroke by decreasing the expression of tight junction proteins and inflammatory cytokines such as TNF-α were observed [ 76 , 77 , 78 ]. Although these studies demonstrated that the introduction of probiotics is associated with anti-inflammatory effects on CHD and stroke, the mechanism of this action is yet to be investigated.…”
Section: Probiotics and Their Potential Role In Cvdmentioning
confidence: 99%
See 1 more Smart Citation